2004
DOI: 10.1093/chemse/bjh012
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone-binding Proteins Contribute to the Activation of Olfactory Receptor Neurons in the Silkmoths Antheraea polyphemus and Bombyx mori

Abstract: The sensilla trichodea of the silkmoth Antheraea polyphemus are innervated by three types of receptor neurons each responding specifically to one of three pheromone components. The sensillum lymph of these sensilla surrounding the sensory dendrites contains three different types of pheromone-binding proteins (PBPs) in high concentrations. The sensilla trichodea of the silkmoth Bombyx mori are supplied by two receptor neurons each tuned specifically to one of the two pheromone components bombykol and bombykal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 29 publications
3
72
0
Order By: Relevance
“…In addition, OBPs might be involved in establishing the olfactory code (Van den Berg and Ziegelberger, 1991;Maida et al, 2003;Pophof, 2004;Matsuo et al, 2007;Laughlin et al, 2008) as well as in stimulus inactivation (Pelosi and Maida, 1995;Ziegelberger, 1995;Kaissling, 2001 . CSPs are more conserved, with a specific motif of four cysteines that form two disulphide bridges between neighbouring residues.…”
Section: Insect Chemosensory Gene Family Evolutionmentioning
confidence: 99%
“…In addition, OBPs might be involved in establishing the olfactory code (Van den Berg and Ziegelberger, 1991;Maida et al, 2003;Pophof, 2004;Matsuo et al, 2007;Laughlin et al, 2008) as well as in stimulus inactivation (Pelosi and Maida, 1995;Ziegelberger, 1995;Kaissling, 2001 . CSPs are more conserved, with a specific motif of four cysteines that form two disulphide bridges between neighbouring residues.…”
Section: Insect Chemosensory Gene Family Evolutionmentioning
confidence: 99%
“…These are the odorant-binding proteins (OBPs) and chemosensory proteins (CSPs). The OBPs are present at high concentrations in the antennae (Steinbrecht et al, 1995;Steinbrecht, 1998) and may contribute to the activation of olfactory receptor neurons (Pophof, 2004). The OBPs are encoded by a multigene family (Robertson et al, 1999;Vogt et al, 1999;Hekmat-Scafe et al, 2000;Vogt , 2002;Galindo and Smith, 2001;Biessmann et al, 2002;Xu et al, 2003;Zhou et al, 2004) and include the pheromone-binding proteins (PBPs), the general odorant-binding proteins (GOBPs), and the antennal-binding proteins (ABPs).…”
Section: Introductionmentioning
confidence: 99%
“…Insect OBPs are small, water soluble molecules expressed in both olfactory and gustatory sensilla, as well as in other specialized tissues . Several studies have demonstrated selective binding of odorants and/or pheromones to different OBPs (Danty et al 1999;Plettner et al 2000;Pophof 2002Pophof , 2004Zhou et al 2004b). It has been proposed that, in addition to playing a role in the activation of odorant-responsive chemosensory neurons, OBPs might work as selective filters in odor recognition (Kim et al 1998) or even participate in signal termination by inactivating odorant molecules (Pelosi and Maida 1995).…”
mentioning
confidence: 99%